Budaya hukum Indonesia menghadapi globalisasi : perlindungan rahasia dagang di bidang farmasi - Priapanca, Cita Citrawinda, 1958- ([Jakarta] : Chandra Pratama, 1999)
Trade secrets law with reference to Indonesian pharmaceutical industry
Revision of the author's thesis (doctoral)--Universitas Indonesia, 1999
Includes bibliographical references (p. 367-409) and index
Keywords: Trade secrets -- Indonesia; Pharmacy -- Law and legislation -- Indonesia; Trade secrets